2019
DOI: 10.1542/peds.2018-2738
|View full text |Cite
|
Sign up to set email alerts
|

A Telehealth-Enhanced Referral Process in Pediatric Primary Care: A Cluster Randomized Trial

Abstract: OBJECTIVES: To improve the mental health (MH) referral process for children referred from primary care to community mental health clinics (CMHCs) by using a community-partnered approach.METHODS: Our partners were a multisite federally qualified health center and 2 CMHCs in Los Angeles County. We randomly assigned 6 federally qualified health center clinics to the intervention or as a control and implemented a newly developed telehealth-enhanced referral process (video orientation to the CMHC and a live videoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 54 publications
(60 reference statements)
0
44
0
Order By: Relevance
“…We did not include messaging/texting in the review because evidence suggests effective public health approaches to child mental health intervention require consideration of multicomponent interventions (e.g., including multiple domains of mental health knowledge, skill training, and practice support in parenting/child/health-worker interventions) (3638). However, existing messaging/texting strategies tend to be used as support or enhancement strategies for interventions, and might be limited in serving as stand-alone mental health intervention strategies in multicomponent interventions (3941). Finally, many adults and parents in LMICs have low literacy (primary or less than primary school education) and do not have smartphones, which make a messaging approach challenging.…”
Section: Methodsmentioning
confidence: 99%
“…We did not include messaging/texting in the review because evidence suggests effective public health approaches to child mental health intervention require consideration of multicomponent interventions (e.g., including multiple domains of mental health knowledge, skill training, and practice support in parenting/child/health-worker interventions) (3638). However, existing messaging/texting strategies tend to be used as support or enhancement strategies for interventions, and might be limited in serving as stand-alone mental health intervention strategies in multicomponent interventions (3941). Finally, many adults and parents in LMICs have low literacy (primary or less than primary school education) and do not have smartphones, which make a messaging approach challenging.…”
Section: Methodsmentioning
confidence: 99%
“…Afterward, 9 articles were excluded. A total of 11 articles were included in this review [39][40][41][42][43][44][45][46][47][48][49]. The reasons for excluding full-text articles are stated in the PRISMA study flowchart (Figure 1).…”
Section: Literature Searchmentioning
confidence: 99%
“…The characteristics of all included studies are reported in Tables 1 and 2. The studies in this review involved a broad range of health conditions, including asthma (2/11, 18%) [46,47], obesity (3/11, 27%) [40,41,44], mental health conditions (1/11, 9%) [48], otitis media (1/11, 9%) [49], skin conditions (1/11, 9%) [43], type 1 diabetes (1/11, 9%) [42], attention deficit hyperactivity disorder (ADHD) (1/11, 9%) [45], and cystic fibrosis-related pancreatic insufficiency (1/11, 9%) [39]. Of the 11 included studies, 9 (82%) were conducted in the United States of America [39][40][41][43][44][45][46][47][48], 1 (9%) was conducted in Italy [42], and 1 (9%) was conducted in Finland [49].…”
Section: Study Characteristicsmentioning
confidence: 99%
“… 38 , 70 Exploration of novel uses of eHealth for providing integrated care services, including expanded use of telemedicine, the use of follow-up text messages and other modalities to prolong the impact of brief in-person mental health interventions, and the integration of on-line treatments for parents and other caregivers into services based in pediatrics. 71 , 72 Development of efficient training and ongoing support programs for community health workers, peer navigators, and others who can both extend the mental health workforce and increase its capacity for providing care in diverse languages and from diverse cultural perspectives. 73 , 74 Studying processes related to practice transformation and interaction across systems, 75 with particular focus on 1) methods for including diverse families in the design and adaptation process of interventions, 76 and 2) efficient methods for providing initial and long-term assistance to practices and systems as they implement and refine integrated care.…”
Section: Introductionmentioning
confidence: 99%
“…Exploration of novel uses of eHealth for providing integrated care services, including expanded use of telemedicine, the use of follow-up text messages and other modalities to prolong the impact of brief in-person mental health interventions, and the integration of on-line treatments for parents and other caregivers into services based in pediatrics. 71 , 72 …”
Section: Introductionmentioning
confidence: 99%